2019
DOI: 10.1093/jas/skz212
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial taxonomic composition of the postpartum cow uterus and vagina prior to artificial insemination1

Abstract: The current study characterized the taxonomic composition of the uterine and vaginal bacterial communities during estrous synchronization up to timed artificial insemination (TAI). Postpartum beef cows (n = 68) were subjected to pre-synchronization step 21 d prior to TAI (day −21), followed by an industry standard 7 Day Co-Synch on day −9 and TAI on day 0. Uterine and vaginal flushes were collected on days −21, −9, and −2 of the protocol and pH was immediately recorded. Pregnancy was determined by transrectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 48 publications
6
53
1
1
Order By: Relevance
“…Currently, there is a knowledge gap describing the effect of the estrous cycle on cattle vaginal microbiota. Ault and colleagues have described that the diversity of the microbiota during luteal phase significantly decreases as the reproductive tract prepares for pregnancy (10). The same authors described differences in Verrucomicrobia, Fusobacteria, and Tenericutes abundances between pregnant and non-pregnant cows (14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is a knowledge gap describing the effect of the estrous cycle on cattle vaginal microbiota. Ault and colleagues have described that the diversity of the microbiota during luteal phase significantly decreases as the reproductive tract prepares for pregnancy (10). The same authors described differences in Verrucomicrobia, Fusobacteria, and Tenericutes abundances between pregnant and non-pregnant cows (14).…”
Section: Introductionmentioning
confidence: 99%
“…Uterine and vaginal cattle microbiota have been determined to contain higher diversity compared to human vaginal microbiota (4,10). Nevertheless, Firmicutes were observed to be frequent and abundant in both (5,11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that the immune system has a vital role in the clearance of uterine diseases, normal reproductive functions, and establishment and maintenance of pregnancy; however, few studies have investigated the reproductive tract immunological environment prior to breeding and the subsequent effect on fertility in beef cattle. Based on published data from the current study, the diversity of bacterial communities of the reproductive tract shifts throughout an estrus synchronization protocol (Ault et al, 2019a) and this is likely due to the taxonomic composition of the bacteria in the uterus and vagina (Ault et al, 2019b). Notably, the relative abundance of multiple genera of bacteria differed between resulting pregnant and non-pregnant cows (Ault et al, 2019b).…”
Section: Introductionmentioning
confidence: 73%
“…Based on published data from the current study, the diversity of bacterial communities of the reproductive tract shifts throughout an estrus synchronization protocol (Ault et al, 2019a) and this is likely due to the taxonomic composition of the bacteria in the uterus and vagina (Ault et al, 2019b). Notably, the relative abundance of multiple genera of bacteria differed between resulting pregnant and non-pregnant cows (Ault et al, 2019b). In the current report, the first objective was to evaluate the concentration of both pro-and antiinflammatory cytokines from uterine and vaginal flush samples throughout an estrus synchronization protocol to determine the potential effects of the immune environment on fertility.…”
Section: Introductionmentioning
confidence: 85%